Resistant Hypertension and Atherosclerotic Renal Artery Stenosis: Effects of Angioplasty on Ambulatory Blood Pressure. A Retrospective Uncontrolled Single-Center Study. Issue 6 (December 2019) - Courand, Pierre-Yves; Dinic, Miriana; Lorthioir, Aurélien; Bobrie, Guillaume; Grataloup, Christine; Denarié, Nicolas; Soulat, Gilles; Mousseaux, Elie; Sapoval, Marc; Azizi, Michel; Amar, Laurence
Abstract : The effect of renal artery angioplasty on blood pressure in patients with true resistant hypertension and atherosclerotic renal artery stenosis has not been fully investigated due to the exclusion of these patients from most trials. In this study, we assessed the benefits of renal angioplasty on daytime ambulatory blood pressure (dABP) in this subgroup of patients. Medical records of our hypertension department were retrospectively analyzed from 2000 to 2016. Seventy-two patients were identified with resistant hypertension (dABP >135 or 85 mm Hg despite at least 3 antihypertensive drugs, including a diuretic) and atherosclerotic renal artery stenosis treated by angioplasty. Atherosclerotic renal artery stenosis was unilateral in 57 patients and bilateral in 15 patients. The mean age of the patients was 67.8±11.2 years; dABP was 157±16/82±10 mm Hg despite 4.0±1.0 antihypertensive treatments; estimated glomerular filtration rate was 52 (41–63) mL/min. After renal angioplasty, dABPM decreased by 14.0±17.3/6.4±8.7 mm Hg ( P <0.001 for both), and the number of antihypertensive treatments decreased to 3.6±1.4 ( P =0.002) with no significant change in estimated glomerular filtration rate. A high baseline systolic dABP and a low body mass index were independent predictors of systolic dABP changes. The decrease in dABP was confirmed in a subgroup of patients at one and 3 years of follow-up (N=31 and N=18 respectively, P ⩽0.001 for systolic and diastolic blood pressure at both visits). In this retrospective uncontrolled single-center study, angioplasty in patients with atherosclerotic renal artery stenosis and with true resistant hypertension significantly decreased dABP, reducing the need for antihypertensive treatment with no change in estimated glomerular filtration rate. Abstract : Supplemental Digital Content is available in the text.